2012
DOI: 10.1055/s-0032-1316342
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cannabis Abuse, Delta-9-tetrahydrocannabinol and Thyroid Function

Abstract: ▼Objective: The aim of this study was to obtain rather rare information about the infl uence of chronic cannabis abuse on thyroid function. Methods: Thyroid function tests (TSH, total T 3 , free T 4 ) of 39 chronic cannabis-dependent subjects (ICD-10) were determined at admission (for in-patient detoxifi cation). In a subgroup, serum levels of thyroid hormones were correlated with the serum levels of delta-9-tetrahydrocannabinol (THC, N = 24) and its major metabolites, THC-OH (N = 16) and THC-COOH (N = 24).Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
(9 reference statements)
1
8
0
1
Order By: Relevance
“…In a cross-sectional, case-control study, chronic cannabis use was associated with visceral adiposity and adipose tissue insulin resistance, but it was not associated with hepatic steatosis, insulin insensitivity, impaired pancreatic -cell function, or glucose intolerance [108]. Chronic cannabis use had no relevant influence on thyroid function (TSH, total T3, and free T4) in humans [109].…”
Section: Iii76 Metabolic Consequencesmentioning
confidence: 93%
“…In a cross-sectional, case-control study, chronic cannabis use was associated with visceral adiposity and adipose tissue insulin resistance, but it was not associated with hepatic steatosis, insulin insensitivity, impaired pancreatic -cell function, or glucose intolerance [108]. Chronic cannabis use had no relevant influence on thyroid function (TSH, total T3, and free T4) in humans [109].…”
Section: Iii76 Metabolic Consequencesmentioning
confidence: 93%
“…Chronic use of cannabis has not been shown to effect thyroid function (100). Acute pancreatitis linked to cannabis use has been reported in a 22-year old male who presented with epigastric pain, nausea, and emesis (101).…”
Section: Medical Adverse Effectsmentioning
confidence: 99%
“…Associations between depression and level of TSH compared to healthy controls have been found in previous studies [ 8 , 10 ]. In studies on cannabis users reduced levels of TSH have been reported [ 19 , 20 ]. There was no significant association between FT4 and any of the diagnostic groups in our cohort.…”
Section: Discussionmentioning
confidence: 99%